The process of authority : the dynamics in transmission and reception of canonical texts - Dušek, Jan; Roskovec, Jan, 1966- (Deuterocanonical and cognate literature studies ;, 2016)
The authority of canonical texts, especially of the Bible, is often described in static definitions. However, the authority of these texts was acquired as well as exercised in a dynamic process of transmission and reception. This book analyzes selected aspects of this historical process. Attention is paid to biblical master-texts and to other texts related to the "biblical worlds" in various historical periods and contexts. The studies examine particular texts, textual variants, translations, paraphrases and other elements in the process of textual transmission. The range covered spans from the Iron Age, through the Old Testament texts, their manuscripts and other texts from Qumran, the Septuagint, down to the New Testament, Apocrypha, Coptic texts, Patristics, and even modern translations of the Bible. The book is particularly intended for those interested in the history of reception and transmission of biblical texts and in the textual criticism.